2007
DOI: 10.1038/sj.emboj.7601605
|View full text |Cite
|
Sign up to set email alerts
|

How much can a T-cell antigen receptor adapt to structurally distinct antigenic peptides?

Abstract: Binding degeneracy is thought to constitute a fundamental property of the T-cell antigen receptor (TCR), yet its structural basis is poorly understood. We determined the crystal structure of a complex involving the BM3.3 TCR and a peptide (pBM8) bound to the H-2K bm8 major histocompatibility complex (MHC) molecule, and compared it with the structures of the BM3.3 TCR bound to H-2K b molecules loaded with two peptides that had a minimal level of primary sequence identity with pBM8. Our findings provide a refine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
104
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 45 publications
0
104
0
Order By: Relevance
“…The concept that cancer cells can be targeted by T cells recognizing self-peptides presented by foreign HLA was first described by Stauss and coworkers (15)(16)(17). Although these and other studies have shown that certain peptides can be specifically recognized when presented on allogeneic HLA (8,9,12,(18)(19)(20)(21)(22)(23), it seemed possible that they represented exceptions, because there is also evidence that allorestricted cells are more promiscuous with regard to peptide recognition (9,18,(24)(25)(26)(27)(28). However, when assessing reactivity to a large number of epitopes at the single-cell level, we did not find evidence suggesting that peptide recognition on foreign HLA generally has a low specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The concept that cancer cells can be targeted by T cells recognizing self-peptides presented by foreign HLA was first described by Stauss and coworkers (15)(16)(17). Although these and other studies have shown that certain peptides can be specifically recognized when presented on allogeneic HLA (8,9,12,(18)(19)(20)(21)(22)(23), it seemed possible that they represented exceptions, because there is also evidence that allorestricted cells are more promiscuous with regard to peptide recognition (9,18,(24)(25)(26)(27)(28). However, when assessing reactivity to a large number of epitopes at the single-cell level, we did not find evidence suggesting that peptide recognition on foreign HLA generally has a low specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The set of tryptic peptides bound by each individual CIMS antibody was thus detected and identified using tandem-mass spectrometry. The results showed that peptides of a median length of 10 amino acids (range [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and with a median pI of 6.5 (range 3.8-12) were captured in a clone-dependent manner (Table I). Noteworthy, as illustrated for the CIMS-17 sister pair, the affinity (K D ) for an experimentally verified captured yeast peptide was found to be in the same range as that observed for the original selection peptide (Table I).…”
Section: Degenerate Peptide-binding Specificitymentioning
confidence: 93%
“…15,16 The available crystal structures of liganded and unliganded TCRs have implied that the flexibility of the TCR combining site facilitates TCR adaptation to rather conformationally constrained MHC-peptide surfaces. [27][28][29] Based on the SH3 work, 25,26 the importance of the affinity for peptide binding promiscuity has been highlighted, and such interactions tend, as might be expected, to be of low affinity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. 9). In one telling case, however, the conformation of the ␣2 helix of the human class I MHC protein HLA-A*0201 (HLA-A2) was shown to undergo a large reorganization upon binding of the A6 TCR (10).…”
mentioning
confidence: 99%